Pricing Higher-Order Moment Systematic Risks in the Nigerian Stock Market: Empirical Analysis from Moment-CAPM, Moment-FF3F and Moment-FF5F. - Oyedeko, Yusuf Olatunji; Mamidu, Aruna Ishola; Kolawole, Olusola Segun (EuroEconomica, 2023)
The purpose of this study is to explore the effect of higher-order moment systematic risks on stock return using Moment-CAPM, Moment-FF3F and Moment-FF5F in the Nigerian stock market. The study sample 90 stocks listed on the Nigerian Group of Exchange as at December 2020. The study covered the period of January 2005 to December 2020 and Fama-MacBeth regression was used as the estimation technique. Evidence from the result showed that coskewness risk has positive significant effect on return under the three-moment factor CAPM, four-moment FF3F and six-moment FF5F. This implies that the coskewness risk is significantly priced in the Nigerian stock market and this means that coskewness risk command premium. Also, this result was supported with the fact that the introduction of coskewness risk significantly improves the explanatory powers of the standard CAPM, FF3F and FF5F models. However, it was revealed that the cokurtosis risk has positive significant effect on return under the seven-moment FF5F but the cokurtosis risk has positive insignificant effect on return under three-moment factor CAPM, four-moment FF3F. In view of this, the study concluded that higher moment systematic risks are also determinants of asset return in the Nigerian stock market which must be taken into consideration in risk-return decision making process. Thus, the study recommends that in the process of making investment decision, the investors should maintain positive skewness risk factor because it will increase the expected return and negative kurtosis which has positive effect on stock return.